ZnO Tetrapods: Synthesis and Applications in Solar Cells - Luting Yan; Ashraf Uddin; Haiwei Wang (Nanomaterials and Nanotechnology)
Zinc oxide (ZnO) tetrapods have received much interest due to their unique morphology, that is, four arms con‐ nected to one centre. Tetrapod networks possess the excellent electronic properties of the ZnO semiconductor, which is attractive for photoelectrode materials in energy- conversion devices because of their advantages in electron extraction and transportation. In this review, we have discussed recent advancements in the field of ZnO tetrapod synthesis, including vapour transport synthesis and the wet chemical method, together with their advantages and disadvantages in terms of morphology control and yield regulation. The developments and improvements in the applications of ZnO nanotetrapods in photovoltaics, including dye-sensitized solar cells and polymer solar cells, are also described. Our aim is to give readers a compre‐ hensive and critical overview of this unique morphology of ZnO, including synthesis control and growth mechanism, and to understand the role of this particular morphology in the development of solar cells. The future research directions in ZnO tetrapods-based solar cell are also discussed.